A Pengembangan Perangkat Pembelajaran Berbasis Discovery Based Unity of Sciences (DBUS) Pada Materi Sistem Reproduksi Kelas XI SMA - Kiky Anggreini Priyanti; Nur Khasanah; Eka Vasia Anggis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2021)
Discovery Based Unity of Sciences (DBUS) learning devices require students to be able to search, identify and find problems that exist around the student's environment with the aim of developing spiritual attitudes and training students' skills. The first thing that the researcher did was to conduct a needs analysis by interviewing biology teachers, analyzing learning tools for XI grade even semesters and distributing questionnaires to students' needs. Based on the results of interviews and analysis of learning tools, it was obtained data that the lesson plans used were not integrated with the unity of science and had not followed SE number 14 of 2019 concerning the simplification of lesson plans, then students' spiritual attitudes and thinking skills were still low and the assessment process was carried out unilaterally by the teacher, so it was not no evaluation or student involvement. Based on these problems, researchers provide solutions to develop learning tools based on Discovery Based Unity of Sciences (DBUS) on reproductive system materials. Learning device products in the form of lesson plans, LKPD and self and peer assessment instruments. It is hoped that students will be able to improve their spiritual attitudes and develop critical thinking skills. This study uses a 4D development model (Define, Design, Development, and Disseminate). The validity test was carried out by education experts, material experts, media experts and experts on the integration of Islamic values. The results of the percentage of RPP are 89.23%, LKPD 91.35% and self and peer assessment instruments are 88.53%. The field test was carried out twice, namely a limited-scale field test and a wide-scale field test. The limited scale field test was carried out by 5 students, for LKPD and self and peer assessment instruments the results obtained were feasibility with a percentage of 85.6%. Then the wide-scale test was carried out by 30 students, for LKPD to obtain a feasibility result with a percentage of 81.3% and the self and peer assessment instrument to obtain a feasibility result with a percentage of 81.2%. The results of the development of DBUS-based learning tools are very suitable for use in learning activities. Keywords : Development of learning tools, Discovery Based Unity of Sciences (DBUS), Reproductive System